The Use of Family Medicinal Plants (TOGA) by Women Farmer Groups Towards Family Income During the Covid-19 Pandemic - Rona Anggrainie; Siska Alfiati; Nurlaili Fitri Gultom (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to determine the contribution of business income from KWT Melati activities to household income in Gunung Ibul Village. This study uses qualitative data and quantitative data. The population in this study were housewives who are members of KWT Melati, a form of women's empowerment activities in Prabumulih City. The sampling technique used is purposive sampling. Purposive Sampling is a sampling technique with certain considerations. The data analysis technique used in this study is Income Analysis and Percentage Descriptive Analysis. Based on the results, it can be concluded that there was a significant increase in income from TOGA at KWT Melati during the covid19 pandemic. However, the contribution of business income of KWT Melati members to the participant's household income was still lacking, one of which was due to the small business scale. Keywords: income, contribution, Family Medicinal Plants (TOGA)